The Role of Leaders and Community Empowerment in Village Autonomy - Rohman, Mujibur; Dwi Istinah, siti Rodhiyah; Widayati, Widayati (Law Development Journal, 2021)
The research aims to examine (1) What are the duties and authorities of village leaders. (2) How is the implementation of the duties and authorities in community empowerment, and (3) How are the obstacles and implementation solutions in Jetak Village, Wedung District, Demak Regency according to Act No. 6 of 2014. The writing method uses Sociological Juridical qualitatively described as an empirical social phenomenon. The results of the study show (1) that the duties and authorities of village leaders can encourage the realization of village autonomy. (2) Implementation of the duties and authorities of the village head in community empowerment with the management of the Village Owned Enterprise (BUM Des) Jetak Sejahtera with community involvement. (3) Barriers: the courage of village leaders is still lacking, income is not maximized, limited human resources, and community participation that is still lacking awareness. Based on the research, it was concluded that business management training is needed, Cooperating in the management of BUM Des. Prosperous, increasing human resources, increasing community participation in order to implement the principle of transparency in all matters. Community empowerment is a major prerequisite to bring the community towards a dynamic economic, social and ecological sustainability.